A TECHNIQUE FOR OPTIMAL PLACEMENT OF DISTRIBUTED GENERATORS IN POWER SYSTEM NETWORKS - HOSSAIN, SHAH MOHAZZEM (DEPARTMENT OF ELECTRICAL, ELECTRONIC AND COMMUNICATION ENGINEERING, 2019)
The modern day societies are becoming more and more dependent on electrical energy. It is the most important part of our day to day life whose demand is increasing continuously. Even with today's advanced power system technologies the losses in the system are very high which are needed to be reduced for higher efficiencies and better receiving end voltages. This is experienced even more in distribution system where there is a direct impact on customer, owing to long radial lines. High R/Xratio of radial network further aggravates the issues. Infelicitous allocation of distributed generators in terms of its bus location may also lead to rise in fault currents, causes voltage variations, intervene in voltage-control processes, increase losses, system capital and operating costs etc. Optimal placement of distributed generators can address these issues significantly by reducing active power losses and enhancing voltage profile in a cost effective manner. Moreover, installation and placement of DG units is not straight-forward and need to be precisely alluded especially for load varying conditions with different variables like power loss, voltage profile, generation cost, load factor and reliability. A lot of complexity arises during optimization of these non-commensurable variables with different types of equality and inequality constraints. In this research, multi-objective optimal placement problem is decomposed into minimization of total active power losses, maximization of qualitative bus voltage profile index enhancement and minimization of total generation cost of a power system network for static and probabilistic dynamic load characteristics with different network constraints. Optimum utilization factor for installed generators and available loads is scaled from the analysis of yearly load-demand curve of a network. The developed algorithm of N-bus system is implemented in IEEE-6 and IEEE-14 bus standard test system to demonstrate the effectiveness of the proposed methods in different loading conditions.